Effect of Q-switched laser surface texturing of titanium on osteoblast cell response - Voisey, K.T.; Scotchford, C.A.; Martin, L.; Gill, H.S. (Elsevier, 2014)
Titanium and its alloys are important biomedical materials. It is known that the surface texture of implanted medical devices affects cell response. Control of cell response has the potential to enhance fixation of implants into bone and, in other applications, to prevent undesired cell adhesion. The potential use of a 100W Q-switched YAG laser miller (DMG Lasertec 60 HSC) for texturing titanium is investigated. A series of regular features with dimensions of the order of tens of micrometers are generated in the surface of titanium samples and the cell response to these features is determined. Characterisation of the laser milled features reveals features with a lengthscale of a few microns superposed on the larger scale structures, this is attributed to resolidification of molten droplets generated and propelled over the surface by individual laser pulses. The laser textured samples are exposed to osteoblast cells and it is seen that cells do respond to the features in the laser textured surfaces.